Understanding How Virtual Reality Can Support Mindfulness Practice: Mixed Methods Study - Seabrook, Elizabeth; Kelly, Ryan; Foley, Fiona; Theiler, Stephen; Thomas, Neil; Wadley, Greg; Nedeljkovic, Maja (JMIR Publications, 2020)
BackgroundRegular mindfulness practice has been demonstrated to be beneficial for mental health, but mindfulness can be challenging to adopt, with environmental and personal distractors often cited as challenges. Virtual reality (VR) may address these challenges by providing an immersive environment for practicing mindfulness and by supporting the user to orient attention to the present moment within a tailored virtual setting. However, there is currently a limited understanding of the ways in which VR can support or hinder mindfulness practice. Such an understanding is required to design effective VR apps while ensuring that VR-supported mindfulness is acceptable to end users. ObjectiveThis study aimed to explore how VR can support mindfulness practice and to understand user experience issues that may affect the acceptability and efficacy of VR mindfulness for users in the general population. MethodsA sample of 37 participants from the general population trialed a VR mindfulness app in a controlled laboratory setting. The VR app presented users with an omnidirectional video of a peaceful forest environment with a guided mindfulness voiceover that was delivered by a male narrator. Scores on the State Mindfulness Scale, Simulator Sickness Questionnaire, and single-item measures of positive and negative emotion and arousal were measured pre- and post-VR for all participants. Qualitative feedback was collected through interviews with a subset of 19 participants. The interviews sought to understand the user experience of mindfulness practice in VR. ResultsState mindfulness (P<.001; Cohen d=1.80) and positive affect (P=.006; r=.45) significantly increased after using the VR mindfulness app. No notable changes in negative emotion, subjective arousal, or symptoms of simulator sickness were observed across the sample. Participants described the user experience as relaxing, calming, and peaceful. Participants suggested that the use of VR helped them to focus on the present moment by using visual and auditory elements of VR as attentional anchors. The sense of presence in the virtual environment (VE) was identified by participants as being helpful to practicing mindfulness. Interruptions to presence acted as distractors. Some uncomfortable experiences were discussed, primarily in relation to video fidelity and the weight of the VR headset, although these were infrequent and minor. ConclusionsThis study suggests that an appropriately designed VR app can support mindfulness practice by enhancing state mindfulness and inducing positive affect. VR may help address the challenges of practicing mindfulness by creating a sense of presence in a tailored VE; by allowing users to attend to visual and auditory anchors of their choice; and by reducing the scope of the content in users' mind-wandering. VR has the unique capability to combine guided mindfulness practice with tailored VEs that lend themselves to support individuals to focus attention on the present moment.